Kajian Historikal Terhadap Perkembangan Perpustakaan di Masa Dinasti Abbasyiyah dan Konteksnya di Masa Sekarang - Rhoni Rodin (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study aims to analyze the history of library development during the Abbasid dynasty and today contect. The method used in this research is the literature method using several sources of books and journals regarding the development of libraries during the Abbasid dynasty. The results showed that the Abbasid dynasty was a milestone in the history of library progress. One of them is Bait al-Hikmah. This institution is not only an educational institution, but also a library institution. With a historical review, this paper attempts to analyze how the development of the Bait al Hikma library during the Abbasid dynasty. Baitul Hikmah, which was initiated by the caliph Harun al-Rashid, became the center of all scientific activities. With the establishment of Baitul Hikmah, knowledge transfer activities have become more advanced. The Caliph succeeded in recruiting the best writers, historians and scientists. The rapid development of the Baitul Hikmah institution has encouraged this institution to expand its role, not only as a translator institution, but also to include: 1) a center for scientific documentation and information services for the community; 2) centers and forums for scientific development activities; and 3) the center for planning and development activities for the implementation of education.